Sistema escolar chileno: características y consecuencias de un modelo orientado al mercado - Cristóbal Villalobos; María Luísa Quaresma (Universidad Autónoma del Estado de México, 2015)
Considering the orientation towards competition and market that many educational systems have taken over last decades, this paper analyzes the characteristics, consequences and implications of the installation of these logics in the educational field from a paradigmatic case study: the Chilean school system. The article shows how this system is organized from the resignation of the role of the state in education, the centrality of private schools, the implementation of demand subsidies and the implementation of strong accountability, which has enhanced and deepened educational segregation, reducing the freedom of choice and generating social mobilization in the country, producing marked changes in the structures, processes and educational outcomes. Against this reality, we discuss the necessity and possibility of building a new educational logic, based on reflectivity, development of critical thinking, intelligent accountability and integral education.